1998 Annual Review of Development Effectiveness - Buckley, Robert (The World Bank, 1999)
The ongoing financial crisis has raised questions about the underpinnings of development assistance and the role of international financial institutions. A new development assistance framework, grounded in partnership, is emerging. That is the backdrop for this year's review, which--as in past years--tracks the World Bank's operational performance based on the findings of recent evaluations. After the backdrop provided in chapter one, the chapters that follow review recent evidence about the Bank's development effectiveness. Chapter 2 describes project and sector performance trends. Chapter 3 considers recent evaluation lessons at the country level. It draws on OED's (Operations Evaluation Department) country assistance evaluations to help draw out the lessons of the ongoing crisis. Chapter 4 draws lessons that can be inferred from thematic studies. The final chapter discusses the implications for Bank operations and evaluation